2014
DOI: 10.1155/2014/296161
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Scores Do Not Correlate with Clinically Adjudicated Categories of Pulmonary Embolism in Critically Ill Patients

Abstract: Pretest probability scores developed outside the ICU do not correlate with adjudicated PE categories in critically ill patients. Research is needed to develop prediction scores for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…In agreement with our results, in a cohort of 70 patients, Katsios et al showed that pretest probability models developed for outpatients do not correlate with clinically suspected PE in critically ill patients. 22,27 Interestingly, as described by Bahloul et al, 28 few patients with confirmed PE have high probability by Wells and Geneva scores compared to previous studies mainly in noncritically ill patients. 8,29 It is possible that in ICU patients, the factors associated with high clinical pretest probability might be different than the factors included in composite scores.…”
Section: Discussionmentioning
confidence: 86%
“…In agreement with our results, in a cohort of 70 patients, Katsios et al showed that pretest probability models developed for outpatients do not correlate with clinically suspected PE in critically ill patients. 22,27 Interestingly, as described by Bahloul et al, 28 few patients with confirmed PE have high probability by Wells and Geneva scores compared to previous studies mainly in noncritically ill patients. 8,29 It is possible that in ICU patients, the factors associated with high clinical pretest probability might be different than the factors included in composite scores.…”
Section: Discussionmentioning
confidence: 86%
“…This finding had already been suggested for patients in critical condition in several clinical trials. (19)(20)(21) Two studies evaluating this aspect in patients hospitalized for COVID-19 infection undergoing CTPA found that the Wells and Geneva scores showed no predictive value for the occurrence of PE, either considering a standard or age-adjusted cutoff point. (22,23) There were no cases of mortality in the group of patients with COVID-19 infection in whom PE was diagnosed, a result that could be attributed to the identification of milder cases (lower PESI) after a more careful diagnostic evaluation in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing PE is often challenging because the signs and symptoms are not specific [14]. There are various scoring systems that determine whether a patient is more or less likely to have a PE.…”
Section: Discussionmentioning
confidence: 99%